The Quranic Vision of the Concept of Politics: A Semantic Study - Hajer, Dr. Haider Mustafa (Thi Qar Arts Journal, 2024)
The concept of politics in the Quran is not merely a terminological release but a conceptual vision. This means that it is an identity capable of formation and transformation based on stages of development and change, which gives it the attribute of vitality and continuity. However, this concept requires components that represent principles relied upon in its formation or in clearly drawing its image in the mind of the recipient. A number of these specifics have been addressed as principles of this concept. The research has reached a number of principles that have interactive, integrative, or alternating relationships. The Quran has paid attention to political affairs as one of the important elements in shaping the features of the state and managing its internal and external affairs. Each nation has its political model that reflects its personality, distinguishing it from others, which in turn reveals the nature of the vision from which the nation interacts with reality in this regard. The Quran, as the foundational text of the Islamic vision and the reflector of its unique personality, contains many principles and concepts that carry political content according to a divine vision or project that can be applied in reality, expressing the essence of humanity or what humanity should be, as it is an entity capable of being shaped through the text. The study took a semantic exploratory approach, utilizing linguistic, interpretive, textual, and analytical data to uncover aspects of this specific vision and what can be applied in reality, and to what extent it can record uniqueness and specificity according to a complex equation, especially after the materialistic or positivist vision has become the dominant vision in the world, carrying a pragmatic dimension in justifying and depicting relationships, which may result in a state of emotional rejection in a person seeking the essence of their humanity.